Innovation in zeolite materials science : proceedings of an international symposium, Nieuwpoort, Belgium, September 13-17, 1987 - Grobet, P. J.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1988)
The proceedings of this zeolite scientific meeting reflect the growing drive to discover new materials. It is evident that zeolite materials science is in a post-ZSM-5 period - pushed by a massive expansion of new compositions and topologies, and the application of new scientific tools. Four new zeolite topologies were detailed at this meeting. Important new trends were the resurgence of interest in computational and theoretical approaches to explain synthesis, sorption and catalytic data, and the increasing use of NMR and high-resolution imaging.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Zeolites; Zéolites.; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Zeolites; Zeolites; Electronic books